Effects of exposure to boars and other gilts on the estrous response after synchronization with altrenogest - Duane L Davis; Jeffrey S Stevenson (Kansas Agricultural Experiment Station Research Reports, 1984)
Estrus was synchronized in gilts by feeding altrenogest for 18 days. All gilts were penned in gestation stalls. Beginning the day before the last altrenogest treatment and continuing until 3 days after treatment, gilts were either exposed to a boar for 2 hr /day, group-penned with other gilts for 2 hr /day, both exposed to a boar and group-penned, or given neither treatment. Boar exposure shortened the interval to estrus but group-penning had no effect. None of the treatments improved the synchrony of estrus.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Boars; Gilts; Estrous; Altrenogest